The formulation of an enhanced recovery programme for patients undergoing laryngectomy. Issue 9 (10th September 2022) - Wilson, G; Nistor, M; Beasley, N
Abstract: Objective: Enhanced recovery programmes have been widely adopted in other surgical disciplines but are not commonplace in head and neck surgery. The authors of this study created a pathway for post-operative laryngectomy patients. Method: A multidisciplinary working group reviewed the literature and agreed standards of care. A retrospective audit was conducted to measure current practice against our new pathway; after programme implementation our performance was reaudited in two prospective cycles, with an education programme and review after the first prospective cycle. Results: Statistically significant improvement in performance was realised in catheter and surgical drain removal, opiate analgesia use, mobilisation, and timeliness of swallow assessment. The rate of hospital acquired pneumonia reduced from 23.1 to 9.5 per cent and length of stay reduced by a median of 5.2 days to 14.8 days (non-significant). Conclusion: The programme improved consistency of patient care across most areas that were measured. Improving patient stoma training needs to be prioritised.